Reverse Time Migration of Vertical Cable Seismic Data to Image Hydrate-Bearing Sediments With High Resolution - Wang, Linfei; Liu, Huaishan; Wang, Zhong; Zhang, Jin; Xing, Lei; Yin, Yanxin (Frontiers in Earth Science, 2021)
Marine Vertical Cable Seismic (VCS) is a promising survey technique for submarine complex structure imaging and reservoir monitoring, which uses vertical arrays of hydrophones deployed near the seafloor to record wavefields in a quiet environment. Recently, we have developed a kind of distributed vertical cable seismic system for exploration and development of natural gas hydrates preserved in shallow sediments under the seafloor. Using this system and air-gun source, we accomplished a 3D VCS yield data acquisition for gas hydrates exploration in Shenhu area, South China Sea. In view of characteristics of VCS geometry, we implement reverse time migration (RTM) on common receiver gather to obtain high-resolution image of marine sediments. Due to the unique acquisition method, it is asymmetrical for the reflection path between the sources and the receivers in VCS survey. Therefore, we apply accurate velocity analysis to the common scatter point (CSP) gathers generated from the common receiver gathers instead of the conventional velocity analysis based on common depth point gathers. RTM with this reliable velocity model results in high resolution images of marine hydrate-bearing sediments in deep water conditions. The imaging section clearly shows not only the bottom simulating reflector (BSR) but also the reflection characteristics of the hydrate-bearing sediments filled with consolidated hydrates. Moreover, its resolution is relative to that of acoustic logging curve from the nearby borehole and this imaging section is well consistent to the synthetic seismogram trace generated by the logging data. All these results reveal that VCS is a great potential technology for exploration and production of marine natural gas hydrates.